People in Northern Bangladesh: Corona Pandemic 2020 Aftermath Action - Sarker, Al-Amin (American International Journal of Social Science Research, 2020)
This paper is to explore Northern Bangladeshi People’s standard of living scenario and how the standard of living could be developed in Rangpur Particularly. The most vulnerable groups in Northern Bangladesh are agricultural wage based marginal farmers; female-headed households and aged people. Their standard of living is very low with a low wage level. As the Coronavirus has become a pandemic in Bangladesh, the northern area is also included in Lockdown condition. The study has been conducted with a structured questionnaire and related statistical tools. The study suggests having more agro-based industrialization in that particular area after Lockdown condition and so on. It also suggests that to promote the standard of living of a particular area they need higher production with higher wage levels that will create higher income and a better standard of living.